PERAN AUDIT FORENSIK DALAM UPAYA PENGUNGKAPAN KORUPSI di INDONESIA - Ayu Kristiani Panggabean; David Adechandra Ashedica Pesudo (ITB AAS INDONESIA, 2023)
The purpose of this study was to find out how forensic audits at the Financial and Development Supervisory Agency Riau Representative in revealing corruption, this qualitative study used primary and secondary methods which from the primary used interview techniques with four employees of the Riau Representative Development and Financial Supervisory Agency (BPKP), People in Pekanbaru and from the secondary use Law number 20 of 2001 concerning